Spinal cord stimulation: An update - Falowski, Steven (Neurotherapeutics, 2008)
Spinal cord stimulation has been used in the treatment of many chronic pain disorders since 1967. In this update, the indications for spinal cord stimulation are reviewed with attention to recent publications. A focused review of the literature on abdominal and visceral pain syndromes is also provided. Furthermore, the technology has evolved from the use of monopolar electrodes to complex electrode arrays. Similarly, the power source has changed from a radio frequency-driven system to a rechargeable impulse generator. These topics are covered, along with a short discussion of implant technique. Finally, we include a review of complications of such therapy. SCS as a technology and therapy continues to evolve.